Effect of stage of harvest and post-harvest ripening of fruits on hybrid seed yield and quality in pumpkin (Cucurbita moschata) - VINOD, K; TOMAR, B S; KADDI, GIRISH; KUMAR, SANJAY (The Indian Journal of Agricultural Sciences, 2014)
The effect of stage of harvest and post-harvest ripening of fruits on seed yield and quality in Pusa Hybrid 1 pumpkin (Cucurbita moschata Duchesne ex Poir) was studied during summer 2008 and 2009 at Seed Production Unit Farm, IARI, New Delhi. Among the six different treatments of harvesting and post-harvest ripening stages, viz. H1-50 DAA, H2 - 60 DAA, H3 - 70 DAA, H1P1 - 50 DAA + 10 PHR, H1P2 - 50 DAA + 20 PHR and H2P1 - 60 DAA + 10 PHR, the fruits harvested at H3 stage outperformed others in respect of fruit weight (3.77 kg), fruit diameter (22.34 cm), cavity length (16.22 cm) and cavity diameter (16.06 cm). However, fruits obtained from H2P1 (60 DAA + 10 PHR) recorded significantly higher number of filled seeds (489.85), total number of seeds (494.35), 100 seed weight (14.68 g) and other seed quality attributes, viz. germination (93.44 %), seedling length (31.26 cm), seedling dry weight (54.96 mg), vigour index - I & II (2921.65 and 5141.64) compared to other treatments. The seed obtained from H2P1 also showed superiority in seed anatomical attributes such as weight of the seed coat (0.294 g), embryo (0.024 g) and cotyledons (1.413 g) as well as protein (399.5 mg/g) and oil (45.5 %) content indicating highest level of development and metabolic gain of the seed.